ORGANOCHLORINE AND ORGANOPHOSPHORUS PESTICIDE RESIDUES IN GRAINS, VEGETABLES AND FRUITS: A REVIEW (FUDMA JOURNAL OF SCIENCES, 2022)
Organochlorin and organophosphorus pesticides are broadly applied in agriculture, primarily to boost crop yields and protect crops from pests to reach the needs of a growing global population. This review aims to assess levels of pesticide residues in grains, fruits, and vegetables from already established secondary data from different authors or journals. The data obtained adequately confirmed the presence of concentrations of Organochlorin and organophosphorus residues in vegetables, grains and fruits. Both high and low concentration levels of pesticide residue were documented based on data obtained which showed application of the synthetic pesticides by farmers.  The high or minute concentration of synthetic pesticides poses adverse health effect on human. This review suggest that consumers of these type of pesticides contaminated food are liable to contact diseases associated with pesticides. Pesticides have been related to damage to the kidneys, liver, and nervous system, birth defects, cancer, immunodeficiency, reproductive process disruption, and altering or interfering with normal endocrine system function. Thereby, the use of natural pesticides as an alternative to synthetic pesticides for pest control is highly recommended for food security and sustainable environmental practices.
Keywords: Organochlorine, Organophosphorus, Pesticides, levels of residues